농정선진화를 위한 지역농업의 발전과제 - 권용대 (한국농촌경제연구원, 2008)
The purpose of this study is to analyze the agricultural policies of central and local governments from the view point of the local agricultural development and to suggest the directions for improving the roles and functions of the participants in local agricultural policies and for agricultural development. To achieve this purpose, case study of three different regions was implemented. The results of this study can be summarized as follows: First of all, enlarging the scale of and systematizing local agricultural production and marketing are the core condition for increasing the efficiency of agricultural production and enhancing marketing power. Second, communications and close cooperation among local government, producers and cooperatives are important to achieve more systematic local agricultural policy implementing process. Third, to ensure successful implementation of agricultural policies of local governments, a player with initiative and drive is necessary to guide local agriculture and make right plans for accommodating the consumers' trends and market changes. Fourth, the support of the central government is very important factor in the success of local government agricultural policies since the state of finance in local governments is in very bad situations. Finally, R&D in agriculture should be more producer oriented in order to make the research results more efficient and accommodate the needs of local agricultural producers. For this purpose, the central government should support the agricultural producers' group financial aid and give these groups the right of choice about the research institutes.